1994
DOI: 10.1002/hlca.19940770115
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of 1H‐Perimidin‐2(3H)‐one and Its Derivatives in the solid state (x‐ray crystallography and CP/MAS 13C‐NMR), in solution (13C‐NMR), and in the gas phase (mass spectrometry)

Abstract: The X-ray crystal and molecular structures of 1 -methyl-1H-perimidin-2(3H)-one (5b) and 1,3-dimethyl-IHperimidin-2(3H)-one (6) were determined. The crystals are built of piles of dimers faced head-to-head in 5b and of alternating independent head-to-tail molecules in 6, both along the 6 axis. Semiempirical calculations at the AM1 level revealed that the eclipsed conformation of the Me groups with respect to the C=O group, found in the crystals, is the most stable. The lack of planarity of the whole molecules i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Another work was published by Ramana and Vairamani 4 who investigated the fragmentation of N-benzyl-o-nitroaniline (9). Ramana and Sudha 5 have also published a detailed study of the fragmentation of N-(2-propynyl)-o-nitroaniline (10).…”
Section: N-alkyl-o-nitroanilinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another work was published by Ramana and Vairamani 4 who investigated the fragmentation of N-benzyl-o-nitroaniline (9). Ramana and Sudha 5 have also published a detailed study of the fragmentation of N-(2-propynyl)-o-nitroaniline (10).…”
Section: N-alkyl-o-nitroanilinesmentioning
confidence: 99%
“…However, semi-empirical calculations for compounds with a similar structure show that, after ionization, the energy gap between two tautomers decreases substantially. 10 The 6-membered ring-closure product a6 can rearrange further by proton transfer from carbon to nitrogen yielding ion a7 (Scheme 3). This process has also to be considered as a reasonable alternative to the a2-a5 sequence.…”
Section: Elimination Of H 2 Omentioning
confidence: 99%
“…A recent survey of the physical methods to study tautomerism [1] reveals that there are no examples of the use of solid state NMR ( 13 C and 15 N) to establish the tautomer present in the solid state in the case of six-membered heterocyclic rings (azines). On the contrary, examples of application to five-membered rings (azoles) abound [2][3][4][5][6][7][8]. To demonstrate the possibilities of CPMAS NMR for the study of the tautomerism of azines, four "classical" compounds were selected: 2-pyridone (1), 4(3H)-pyrimidone (2), uracil (3) and cytosine (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not report a structure [14]. The structures of 1-methyl-1H-perimidin-2(3H)-one and 1,3-dimethyl-IH-perimidin-2(3H)-one were reported by Claramunt et al [15] Another example of 2-methylsulfanyl-1H-perimidin-3-ium iodide was reported by Ghorbani [16]. However, mechanistic details are not available for the formation of perimidines or their derivatives.…”
Section: Introductionmentioning
confidence: 99%